PERANCANGAN SISTEM KENDALI PADA SISTEM KEAMANAN SEPEDA MOTOR DENGAN MIKROKONTROLER ESP32 - Assubhi, Moh Hanif; Rahmadewi, R (Aisyah Journal Of Informatics and Electrical Engineering (A.J.I.E.E), 2024)
Along with the rapid development of technology, of course, making the security system more sophisticated, efficient and innovative. Internet of Things (IoT)-based security is one of the options for implementing technology in the security sector. With the existence of IoT, every community can keep their vehicle safely through a protection or monitoring system. In this study, the authors design and manufacture a Motorcycle Security System using Face recognition and Bluetooth-based Keyless as a motorcycle lock and a SW-420 vibration sensor as a theft detection. The theft detection system is also supported by a telegram notification service when there is an indication of theft on a motorcycle. The motorcycle protection control system with Keyless on this System can function only at a distance of 0 – 8.35 meters between the iTag BLE module and the ESP32 microcontroller. In other control systems, face recognition verification services can be carried out at a minimum user distance of 25cm and a maximum user distance of 50cm. While the protection system with a vibration sensor has a working logic truth of 100%. In the next development, a device with better hardware specifications is needed so that the performance of the control system has a wider range of detection values